ECONOMICAL ANALYSIS OF EFFICIENCY OF RICE FARMS IN AL-NAJAF ALASHRAF FOR THE AGRICULTURAL SEASON 2017 - & et al., kery (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The paper were carried on rice farmers in Al-Najaf Al-Ashraf province. It aimed for studying economical efficiency for a random stratified sample of 5%. 235 forms brand have been collected. The paper depended, to maintain its aims, on using Data Envelopment Analysis (DEA) upon the production and costs functions of farms of the research sample under discussion. Many conclusions have been achieved The results of estimating the technical efficiency upon production function refer that the jasmine Anbar 33, Anbar Al Baraka, 84.2%, 88.9%, 86.4%. The total economic efficiency of these cultivars were 30, 26 and 10, respectively Depending on the variables of the costs function, the results of Data Envelopment Analysis (DEA) showed that the economical,  technical, and Allocative  average efficiency of jasmine brand  farms were 84.2%, 70.2%, and 60% respectively. While farm of Anbar brand 33, the economical, technical, and allocative average efficiency were about 88.9%, 70.7%, and 79.1% respectively. Finally, the technical, economical, and allocative average efficiency for Anbar AL Baraka brand farmers were  86.4%, 84.9, and 73.9% respectively.